FAKTOR RISIKO GIZI BURUK BALITA DI DUSUN TERUMAN BANTUL - Ari Sulistyawati (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Nutritional status is a measure of success in meeting children's nutritional needs. In the past few years the target of reducing under-five nutritional status has not been significant. The impact of malnutrition on children is difficult to correct in adulthood. The prevalence of malnutrition in Bantul Regency in 2017 is 0.41%. Research on the factors of illness history, maternal employment status, maternal education status, gender, number of family members, parenting, underweight birth weight, birth length, pattern of health care for children under five, socioeconomic, maternal knowledge about nutrition in the incidence of malnutrition was very needed. The purpose of this study was to determine the factors associated with the incidence of malnutrition. This research is a quantitative study with a cross sectional approach. The population of toddlers in Teruman Hamlet is 980 children, a sample of 108 toddlers taken through purposive sampling method. Data obtained through interviews and KMS documentation. Univariate data were analyzed by simple descriptive, bivariate data were analyzed using Chi Square test. This study found 5% of malnourished children under five. Based on the bivariate test, it was found that factors related to the incidence of primary caregiver malnutrition, number of family members, parenting patterns, and health care patterns of children under five (p <0.05). It is expected that the family can improve the quality of care for children under five, supported by assistance from health cadres and Public health care.